Routledge international encyclopedia of queer culture - Gerstner, David A. (Routledge, 2006)
The Routledge International Encyclopedia of Queer Culture covers gay, lesbian, bisexual, transgender and queer (GLBTQ) life and culture post-1945, with a strong international approach to the subject.The scope of the work is extremely comprehensive, with entries falling into the broad categories of Dance, Education, Film, Health, Homophobia, the Internet, Literature, Music, Performance, and Politics. Slang is also covered. The international contributors come from a wide array of backgrounds: scholars, journalists, artists, doctors, scientists, lawyers, activists, and an enormous range of ideologies and points of view are represented. Major entries provide in-depth information and consider the intellectual and cultural implications of their subjects in a global context. Information is completely up-to-date, including full coverage and analysis of such current or ongoing issues as same-sex marriage/civil union and the international AIDS epidemic. Additionally, there are important appendices covering international sodomy laws and archival institutions, which will be of great value to researchers. The Encyclopedia is fully cross-referenced and many entries carry a bibliography. Where possible internet references have been given and there is a full index.The combination of its wide scope, determined international coverage and appendices make the Routledge International Encyclopedia of Queer Culture a uniquely ambitious work and an extremely rich source of information. It is a priority addition for all libraries serving scholars and students with an interest in GLBTQ culture, history and politics across the disciplines.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; incontournable; outils; ouvrages de références; queer; ressource en ligne; thématiques

Sexe et genre - Mathieu, Nicole-Claude (Dictionnaire critique du féminisme, 2000)
Keywords: 1900-1999; anthropologie; approches et analyses; cours; discipline; fem1000; incontournable; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines